Anti-aging polyvinyl chloride sheet and preparation method thereof

By optimizing the composition ratio and process in the polyvinyl chloride sheet, using components such as organic tin stabilizers, liquid calcium and zinc stabilizers, ACR additives, modified hyperbranched polyester plasticizers and composite hydrotalcite, the problem of performance degradation of polyvinyl chloride sheets under long-term light is solved, and a polyvinyl chloride sheet with high strength, high flame retardancy and aging resistance is achieved.

CN119735902AActive Publication Date: 2025-04-01LINHAI HAICHANG PLASTIC

Patent Information

Application Number
CN202510259173.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-06
Publication Date
2025-04-01
Estimated Expiration
2045-03-06

AI Technical Summary

Technical Problem

Polyvinyl chloride sheets are prone to surface discoloration, mechanical properties, cracking and powdering under long-term light, and excessive addition of existing anti-aging agents affects the overall performance of the material.

Method used

The optimized composition ratio and process are used to prepare aging-resistant polyvinyl chloride sheets using organic tin stabilizers, liquid calcium and zinc stabilizers, ACR additives, modified hyperbranched polyester plasticizers and composite hydrotalcites.

Benefits of technology

The mechanical strength improvement, high flame retardancy and aging resistance of polyvinyl chloride sheets are achieved, extending the service life of the material and improving safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of polyvinyl chloride, in particular to an anti-aging polyvinyl chloride sheet and a preparation method thereof.The anti-aging polyvinyl chloride sheet is characterized in that one of an organic tin stabilizer and a liquid calcium-zinc stabilizer is introduced into a polyvinyl chloride base material to serve as a stabilizer, the processability of the polyvinyl chloride base material is improved by selecting an ACR auxiliary agent, and ethylene bis stearamide serves as an anti-sticking agent; one or more of oxidized polyethlene wax, polyol ester and stearate are used as a lubricant; 2-carboxyethyl phenyl phosphinic acid and 1, 1, 1-trimethylolpropane are used as raw materials to synthesize hyperbranched polyester, then a hydroxyl-containing s-triazine ultraviolet absorbent is grafted, and the modified hyperbranched polyester plasticizer is obtained and used for plastifying sheets. The preparation method comprises the following steps: selecting hydrotalcite-like compound as a filler, selecting carboxylated silsesquioxane as a modifier through a stripping recombination method to obtain carboxylated hydrotalcite-like compound, and then grafting a hydroxyl-containing s-triazine ultraviolet absorbent, thereby greatly enhancing the flame retardance, fire resistance and weather resistance of the sheet and enhancing the use safety of the sheet.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyvinyl chloride, in particular to an aging-resistant polyvinyl chloride sheet and a preparation method thereof. Background Art

[0002] Polyvinyl chloride, which has the characteristics of high strength, good corrosion resistance, good insulation and low price, is widely used in various fields of daily life. Affected by the synthesis process and conditions, polyvinyl chloride is prone to surface discoloration, reduced mechanical properties, and even cracking and powdering under long-term light.

[0003] In the existing market, anti-aging agents and antioxidants are usually added to improve the aging resistance of polyvinyl chloride. However, adding a large amount of them can easily affect the comprehensive performance of polyvinyl chloride materials. At the same time, in order to further expand the scope of use of polyvinyl chloride sheets, functional requirements such as flame retardancy and fire resistance are also gradually increasing. Summary of the invention

[0004] The object of the present invention is to provide an aging-resistant polyvinyl chloride sheet and a preparation method thereof, so as to solve the problems in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: An aging-resistant polyvinyl chloride sheet comprises the following components, measured by weight: 88-102 parts of polyvinyl chloride resin, 2-4 parts of stabilizer, 6-9 parts of ACR additive, 3-7 parts of composite hydrotalcite, 5-10 parts of modified hyperbranched polyester plasticizer, 0.5-1 parts of ethylene bis stearamide and 0.2-0.6 parts of lubricant.

[0006] Furthermore, the stabilizer is one of an organic tin stabilizer and a liquid calcium zinc stabilizer, or a combination thereof.

[0007] Furthermore, the lubricant is one or more of oxidized polyethylene wax, polyol ester, and stearate.

[0008] Further, the preparation of the modified hyperbranched polyester plasticizer comprises the following steps: 1) In a nitrogen atmosphere, 2-carboxyethylphenylphosphinic acid and 1,1,1-trimethylolpropane were mixed, the temperature was raised to 158-162°C and kept warm for 7-8 hours, the nitrogen was stopped, the vacuum was evacuated to 0.098MPa and kept warm for 2 hours, the mixture was poured out while hot, and cooled to obtain a hyperbranched polyester; 2) The hyperbranched polyester is heated to melt, and a mixture of a hydroxyl-containing triazine UV absorber, toluene, and p-toluenesulfonic acid is added, and the mixture is kept at 108-110°C for 5-6 hours, and the mixture is evacuated to 0.098 MPa, stirred for 1-2 hours, cooled, and dried to obtain a modified hyperbranched polyester plasticizer.

[0009] Furthermore, the mass ratio of the hyperbranched polyester to the hydroxyl-containing s-triazine ultraviolet absorber is 11:3.

[0010] Furthermore, the preparation of the composite hydrotalcite-like substance comprises the following steps: (1) Vinyl trimethoxysilane, acetone, concentrated hydrochloric acid and deionized water are mixed, kept at 40-50°C for 44-48 hours, washed and filtered to obtain vinyl silsesquioxane; vinyl silsesquioxane, methacrylic acid, sodium dodecyl sulfonate and deionized water are mixed, ultrasonically treated for 10-15 minutes, ammonium persulfate is added, kept at 55-65°C for 25-35 minutes, ammonium persulfate, sodium bisulfate, deionized water and methacrylic acid are added, and kept warm for 3-4 hours to obtain carboxylated silsesquioxane; (2) Mixing carboxylated silsesquioxane and deionized water, adding hydrotalcite-like powder, and ultrasonically treating for 10-15 minutes to obtain a suspension; adding the suspension to carboxylated silsesquioxane, stirring at 55-65° C. for 1-2 hours, and drying to obtain a carboxylated hydrotalcite-like powder; (3) Mix the carboxylated hydrotalcite, the hydroxyl-containing s-triazine ultraviolet absorber and toluene, add p-toluenesulfonic acid, raise the temperature to 108-110°C and keep it for 2-3 hours to obtain a composite hydrotalcite.

[0011] Furthermore, the mass ratio of the carboxylated hydrotalcite to the hydroxyl-containing s-triazine ultraviolet absorber is 2.5:1.4.

[0012] Furthermore, the preparation of the hydroxyl-containing s-triazine ultraviolet absorber comprises the following steps: A. Mix cyanuric chloride and chlorobenzene, add anhydrous aluminum chloride in an ice water bath, stir for 20-30 minutes, add m-xylene, keep warm for 2-3 hours, add dilute hydrochloric acid, extract with chlorobenzene twice, dry, rotary evaporate, cool, and filter to obtain 2-chloro-4,6-di(2',4'-dimethylphenyl)-1,3,5-s-triazine; B. Mix 2-chloro-4,6-di(2',4'-dimethylphenyl)-1,3,5-s-triazine and chlorobenzene, add anhydrous aluminum chloride in an ice-water bath, stir for 20-30 minutes, add resorcinol, heat to 78-82℃ and keep warm for 1-2 hours, add dilute hydrochloric acid, distill, filter, and recrystallize twice with toluene to obtain 2-(2',4'-dihydroxyphenyl)-4,6-di(2',4'-dimethylphenyl)-1,3,5-s-triazine; C. Mix 2-(2',4'-dihydroxyphenyl)-4,6-bis(2',4'-dimethylphenyl)-1,3,5-s-triazine, N,N-dimethylformamide and sodium hydroxide, heat to 78-82°C in a water bath, add epichlorohydrin, keep warm for 5-6h, reduce pressure, add aqueous ammonium chloride solution, extract with dichloromethane for 3 times, dry, concentrate, recrystallize with ethanol and dichloromethane solution with a volume ratio of 10:1 to obtain 2-(4,6-bis(2',4'-dimethylphenyl)-1,3,5-triazine-2-yl)-5-glycidyl ether phenol; D. Mix 2-(4,6-bis(2',4'-dimethylphenyl)-1,3,5-triazine-2-yl)-5-glycidyl ether phenol, N,N-dimethylformamide, ethyltriphenylphosphonium bromide, n-dodecanol and n-tridecanol, heat to 88-92°C in a water bath and keep warm for 22-24 hours, reduce the pressure, add deionized water, extract with ethyl acetate, dry and concentrate, reflux with ethanol for 10-20 minutes, cool and obtain a hydroxyl-containing s-triazine ultraviolet absorber.

[0013] Furthermore, a method for preparing an aging-resistant polyvinyl chloride sheet comprises the following steps: Put polyvinyl chloride resin, stabilizer, ACR additive, modified hyperbranched polyester plasticizer, composite hydrotalcite, ethylene bis stearamide and lubricant into a high-speed mixer, mix and stir evenly, then extrude granulate and press to form a sheet to obtain an aging-resistant polyvinyl chloride sheet.

[0014] Furthermore, the working conditions of the high-speed mixer are: preheating to 118°C before feeding.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The invention provides an aging-resistant polyvinyl chloride sheet and a preparation method thereof. The polyvinyl chloride sheet with good mechanical strength, high flame retardancy and aging resistance is prepared by optimizing components and processes.

[0016] Introduce one of organic tin stabilizer and liquid calcium zinc stabilizer as stabilizer into polyvinyl chloride base material to improve the thermal stability of polyvinyl chloride, select ACR additive to improve its processability, use ethylene bisstearamide as anti-sticking agent, use one or more of oxidized polyethylene wax, polyol ester and stearate as lubricant to improve the fluidity of base material and improve its plastic processability.

[0017] In order to improve the negative effects of the addition of a large number of existing small molecule plasticizers, such as migration and decreased mechanical properties, and to simultaneously meet the requirements of improving processing fluidity, maintaining mechanical properties and improving aging resistance, the present invention uses 2-carboxyethylphenylphosphinic acid and 1,1,1-trimethylolpropane as raw materials to synthesize a hyperbranched polyester, and then grafts the hyperbranched polyester with a hydroxyl-containing s-triazine ultraviolet absorber to obtain a modified hyperbranched polyester plasticizer for plasticizing polyvinyl chloride sheets, while greatly improving the flame retardancy and weather resistance of the sheets; wherein the hydroxyl-containing The s-triazine UV absorber is made of cyanuric chloride as raw material, which is subjected to the Friedel-Crafts reaction to generate 2-(2',4'-dihydroxyphenyl)-4,6-di(2',4'-dimethylphenyl)-1,3,5-s-triazine, which is then condensed with epichlorohydrin and then reacted with dodecanol and trialkyl alcohol. Compared with the common benzotriazole and benzophenone UV absorbers on the market, it has the advantages of strong UV absorption at 280-380nm, lighter color, high temperature resistance and better solubility.

[0018] In the present invention, hydrotalcite-like materials are selected as fillers to improve the thermal stability and flame retardancy of the sheet. In order to further improve the uniformity of the dispersion of hydrotalcite-like materials in the sheet, the hydrotalcite-like materials are modified. Carboxylated silsesquioxane with flame retardancy is selected as a modifier through a stripping and recombination method to obtain synergistic flame retardancy to obtain carboxylated hydrotalcite-like materials. Then, a hydroxyl-containing s-triazine ultraviolet absorber is grafted to greatly improve the flame retardancy and weather resistance of the sheet, improve the use safety of the sheet, and extend the service life of the sheet. DETAILED DESCRIPTION

[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] It should be noted that if the embodiments of the present invention involve directional indications such as up, down, left, right, front, and back, the directional indication is only used to explain a specific posture such as the relative position relationship between the components, the movement status, etc. If the specific posture changes, the directional indication will also change accordingly. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the protection scope required by the present invention.

[0021] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.

[0022] Embodiment 1: A method for preparing an aging-resistant polyvinyl chloride sheet, comprising the following steps: putting polyvinyl chloride resin, stabilizer, ACR additive, modified hyperbranched polyester plasticizer, composite hydrotalcite, ethylene bis stearamide, and lubricant into a high-speed mixer, mixing and stirring, and then extruding and granulating, and pressing and tableting to obtain an aging-resistant polyvinyl chloride sheet; Working conditions of high-speed mixer: preheat to 118℃ before adding materials; The composition comprises the following components by weight: 88 parts of polyvinyl chloride resin, 2 parts of stabilizer, 6 parts of ACR additive, 3 parts of composite hydrotalcite, 5 parts of modified hyperbranched polyester plasticizer, 0.5 parts of ethylene bis stearamide, and 0.2 parts of lubricant; The stabilizer is methyl tin mercaptan; the lubricant is oxidized polyethylene wax; The preparation of the modified hyperbranched polyester plasticizer comprises the following steps: 1) In a nitrogen atmosphere, 0.3 mol 2-carboxyethylphenylphosphinic acid and 0.2 mol 1,1,1-trimethylolpropane were mixed, the temperature was raised to 158°C and kept for 8 hours, the nitrogen was stopped, the vacuum was evacuated to 0.098 MPa and kept for 2 hours, the mixture was poured out while hot, and cooled to obtain a hyperbranched polyester; 2) 11 g of hyperbranched polyester was heated to melt, 3 g of hydroxyl-containing s-triazine UV absorber, 250 mL of toluene, and 0.5 g of p-toluenesulfonic acid were added, the temperature was raised to 108°C and kept for 5 h, the temperature was evacuated to 0.098 MPa, stirred for 1 h, cooled, and dried to obtain a modified hyperbranched polyester plasticizer; The preparation of the composite hydrotalcite-like material comprises the following steps: (1) 14 mL of vinyl trimethoxysilane, 135 mL of acetone, 22 mL of concentrated hydrochloric acid, and 25 mL of deionized water were mixed, kept at 40 ° C for 48 hours, washed, and filtered to obtain vinyl silsesquioxane; 0.2 g of vinyl silsesquioxane, 3.3 g of methacrylic acid, 0.2 g of sodium dodecyl sulfonate, and 16 mL of deionized water were mixed, ultrasonically treated for 15 minutes, 0.4 g of ammonium persulfate was added, and the mixture was kept at 55 ° C for 35 minutes. 0.7 g of ammonium persulfate, 0.2 g of sodium bisulfate, 8 mL of deionized water, and 3.3 g of methacrylic acid were added, and the mixture was kept at 55 ° C for 35 minutes. , 8 mL of deionized water and 3.3 g of methacrylic acid were added, and the mixture was kept warm for 3 hours to obtain carboxylated silsesquioxane; (2) 10 g of carboxylated silsesquioxane and 25 mL of deionized water were mixed, 1 g of hydrotalcite powder was added, and ultrasonic treatment was performed for 10 min to obtain a suspension; the suspension was added to 7.5 g of carboxylated silsesquioxane, and stirred at 55 °C for 2 h to obtain a carboxylated hydrotalcite; (3) Mix 2.5 g of carboxylated hydrotalcite, 1.4 g of hydroxyl-containing triazine ultraviolet absorber, and 50 mL of toluene, add 0.1 g of p-toluenesulfonic acid, and heat to 108 °C for 3 h to obtain a composite hydrotalcite; The preparation of the hydroxyl-containing s-triazine ultraviolet absorber comprises the following steps: A. Mix 9.2g of cyanuric chloride and 125mL of chlorobenzene, add 20g of anhydrous aluminum chloride in an ice water bath, stir for 20min, add 10.6g of m-xylene, keep warm for 2h, add 100mL of 2% dilute hydrochloric acid, extract twice with 100mL of chlorobenzene, dry, rotary evaporate, cool, and filter to obtain 2-chloro-4,6-di(2',4'-dimethylphenyl)-1,3,5-s-triazine; B. Mix 9.7g 2-chloro-4,6-bis(2',4'-dimethylphenyl)-1,3,5-s-triazine and 100mL chlorobenzene, add 4g anhydrous aluminum chloride in an ice-water bath, stir for 20min, add 3.6g resorcinol, heat to 78℃ and keep warm for 2h, add 100mL 2% dilute hydrochloric acid, distill, filter, and recrystallize twice with toluene to obtain 2-(2',4'-dihydroxyphenyl)-4,6-bis(2',4'-dimethylphenyl)-1,3,5-s-triazine; C. Mix 4g 2-(2',4'-dihydroxyphenyl)-4,6-bis(2',4'-dimethylphenyl)-1,3,5-s-triazine, 35mL N,N-dimethylformamide, and 0.5g sodium hydroxide, heat to 78°C in a water bath, add 1.2g epichlorohydrin, keep warm for 6h, reduce pressure, add 100mL ammonium chloride aqueous solution, extract with dichloromethane 3 times, dry, concentrate, and recrystallize with ethanol and dichloromethane solution with a volume ratio of 10:1 to obtain 2-(4,6-bis(2',4'-dimethylphenyl)-1,3,5-triazine-2-yl)-5-glycidyl ether phenol; D. Mix 4.5 g of 2-(4,6-bis(2',4'-dimethylphenyl)-1,3,5-triazine-2-yl)-5-glycidyl ether phenol, 50 mL of N,N-dimethylformamide, 0.8 g of ethyltriphenylphosphonium bromide, 1.5 g of n-dodecanol, and 0.8 g of n-tridecanol, heat to 88°C in a water bath and keep warm for 24 h, reduce the pressure, add 75 mL of deionized water, extract with ethyl acetate, dry, concentrate, reflux with ethanol for 10 min, and cool to obtain a hydroxyl-containing s-triazine ultraviolet absorber.

[0023] Embodiment 2: A method for preparing an aging-resistant polyvinyl chloride sheet, comprising the following steps: putting polyvinyl chloride resin, stabilizer, ACR additive, modified hyperbranched polyester plasticizer, composite hydrotalcite, ethylene bisstearamide, and lubricant into a high-speed mixer, mixing and stirring, and then extruding and granulating, and pressing and tableting to obtain an aging-resistant polyvinyl chloride sheet; Working conditions of high-speed mixer: preheat to 118℃ before adding materials; The composition comprises the following components by weight: 93 parts of polyvinyl chloride resin, 3 parts of stabilizer, 7 parts of ACR additive, 5 parts of composite hydrotalcite, 8 parts of modified hyperbranched polyester plasticizer, 0.8 parts of ethylene bis stearamide, and 0.4 parts of lubricant; The stabilizer is methyl tin mercaptan; the lubricant is oxidized polyethylene wax; The preparation of the modified hyperbranched polyester plasticizer comprises the following steps: 1) In a nitrogen atmosphere, 0.3 mol 2-carboxyethylphenylphosphinic acid and 0.2 mol 1,1,1-trimethylolpropane were mixed, the temperature was raised to 160°C and kept for 7.5 hours, the nitrogen was stopped, the vacuum was evacuated to 0.098 MPa and kept for 2 hours, the mixture was poured out while hot, and cooled to obtain a hyperbranched polyester; 2) 11 g of hyperbranched polyester was heated to melt, 3 g of hydroxyl-containing s-triazine UV absorber, 250 mL of toluene, and 0.5 g of p-toluenesulfonic acid were added, the temperature was raised to 109°C and kept for 5.5 h, the pressure was evacuated to 0.098 MPa, stirred for 1.5 h, cooled, and dried to obtain a modified hyperbranched polyester plasticizer; The preparation of the composite hydrotalcite-like material comprises the following steps: (1) 14 mL of vinyl trimethoxysilane, 135 mL of acetone, 22 mL of concentrated hydrochloric acid, and 25 mL of deionized water were mixed, kept at 45 ° C for 46 hours, washed, and filtered to obtain vinyl silsesquioxane; 0.2 g of vinyl silsesquioxane, 3.3 g of methacrylic acid, 0.2 g of sodium dodecyl sulfonate, and 16 mL of deionized water were mixed, ultrasonically treated for 13 minutes, 0.4 g of ammonium persulfate was added, and the mixture was kept at 60 ° C for 30 minutes. 0.7 g of ammonium persulfate, 0.2 g of sodium bisulfate, 8 mL of deionized water, and 3.3 g of methacrylic acid were added, and the mixture was kept at 60 ° C for 30 minutes. , 3.3 g of methacrylic acid was added, and the mixture was kept warm for 3.5 hours to obtain carboxylated silsesquioxane; (2) 10 g of carboxylated silsesquioxane and 25 mL of deionized water were mixed, 1 g of hydrotalcite powder was added, and ultrasonic treatment was performed for 13 min to obtain a suspension; the suspension was added to 7.5 g of carboxylated silsesquioxane, and stirred at 60 ° C for 1.5 h to obtain a carboxylated hydrotalcite; (3) 2.5 g of carboxylated hydrotalcite, 1.4 g of hydroxyl-containing triazine ultraviolet absorber, and 50 mL of toluene were mixed, 0.1 g of p-toluenesulfonic acid was added, and the temperature was raised to 109 ° C and kept for 2.5 h to obtain a composite hydrotalcite; The preparation of the hydroxyl-containing s-triazine ultraviolet absorber comprises the following steps: A. Mix 9.2g of cyanuric chloride and 125mL of chlorobenzene, add 20g of anhydrous aluminum chloride in an ice water bath, stir for 25min, add 10.6g of m-xylene, keep warm for 2.5h, add 100mL of 2% dilute hydrochloric acid, extract twice with 100mL of chlorobenzene, dry, rotary evaporate, cool, and filter to obtain 2-chloro-4,6-di(2',4'-dimethylphenyl)-1,3,5-s-triazine; B. Mix 9.7g 2-chloro-4,6-bis(2',4'-dimethylphenyl)-1,3,5-s-triazine and 100mL chlorobenzene, add 4g anhydrous aluminum chloride in an ice water bath, stir for 20-30min, add 3.6g resorcinol, heat to 80℃ and keep warm for 1.5h, add 100mL 2% dilute hydrochloric acid, distill, filter, recrystallize twice with toluene to obtain 2-(2',4'-dihydroxyphenyl)-4,6-bis(2',4'-dimethylphenyl)-1,3,5-s-triazine; C. Mix 4g 2-(2',4'-dihydroxyphenyl)-4,6-bis(2',4'-dimethylphenyl)-1,3,5-s-triazine, 35mL N,N-dimethylformamide, and 0.5g sodium hydroxide, heat to 80°C in a water bath, add 1.2g epichlorohydrin, keep warm for 5.5h, reduce pressure, add 100mL ammonium chloride aqueous solution, extract with dichloromethane three times, dry, concentrate, and recrystallize with ethanol and dichloromethane solution with a volume ratio of 10:1 to obtain 2-(4,6-bis(2',4'-dimethylphenyl)-1,3,5-triazine-2-yl)-5-glycidyl ether phenol; D. Mix 4.5 g of 2-(4,6-bis(2',4'-dimethylphenyl)-1,3,5-triazine-2-yl)-5-glycidyl ether phenol, 50 mL of N,N-dimethylformamide, 0.8 g of ethyltriphenylphosphonium bromide, 1.5 g of n-dodecanol, and 0.8 g of n-tridecanol, heat to 90°C in a water bath and keep warm for 23 h, reduce the pressure, add 75 mL of deionized water, extract with ethyl acetate, dry, concentrate, reflux with ethanol for 15 min, and cool to obtain a hydroxyl-containing s-triazine UV absorber.

[0024] Embodiment 3: A method for preparing an aging-resistant polyvinyl chloride sheet, comprising the following steps: putting polyvinyl chloride resin, stabilizer, ACR additive, modified hyperbranched polyester plasticizer, composite hydrotalcite, ethylene bisstearamide, and lubricant into a high-speed mixer, mixing and stirring, and then extruding and granulating, and pressing and tableting to obtain an aging-resistant polyvinyl chloride sheet; Working conditions of high-speed mixer: preheat to 118℃ before adding materials; The composition comprises the following components by weight: 102 parts of polyvinyl chloride resin, 4 parts of stabilizer, 9 parts of ACR additive, 7 parts of composite hydrotalcite, 10 parts of modified hyperbranched polyester plasticizer, 1 part of ethylene bis stearamide, and 0.6 parts of lubricant; The stabilizer is methyl tin mercaptan; the lubricant is oxidized polyethylene wax; The preparation of the modified hyperbranched polyester plasticizer comprises the following steps: 1) In a nitrogen atmosphere, 0.3 mol 2-carboxyethylphenylphosphinic acid and 0.2 mol 1,1,1-trimethylolpropane were mixed, the temperature was raised to 162°C and kept for 7 hours, the nitrogen was stopped, the vacuum was evacuated to 0.098 MPa and kept for 2 hours, the mixture was poured out while hot, and cooled to obtain a hyperbranched polyester; 2) 11 g of hyperbranched polyester was heated to melt, 3 g of hydroxyl-containing s-triazine UV absorber, 250 mL of toluene, and 0.5 g of p-toluenesulfonic acid were added, the temperature was raised to 110° C. and kept for 6 h, the pressure was evacuated to 0.098 MPa, stirred for 2 h, cooled, and dried to obtain a modified hyperbranched polyester plasticizer; The preparation of the composite hydrotalcite-like material comprises the following steps: (1) 14 mL of vinyl trimethoxysilane, 135 mL of acetone, 22 mL of concentrated hydrochloric acid, and 25 mL of deionized water were mixed, kept at 50 ° C for 44 h, washed, and filtered to obtain vinyl silsesquioxane; 0.2 g of vinyl silsesquioxane, 3.3 g of methacrylic acid, 0.2 g of sodium dodecyl sulfonate, and 16 mL of deionized water were mixed, ultrasonically treated for 15 min, 0.4 g of ammonium persulfate was added, and the mixture was kept at 65 ° C for 25 min. 0.7 g of ammonium persulfate, 0.2 g of sodium bisulfate, 8 mL of deionized water, and 3.3 g of methacrylic acid were added, and the mixture was kept at 65 ° C for 25 min. , 8 mL of deionized water and 3.3 g of methacrylic acid were added, and the mixture was kept warm for another 4 h to obtain carboxylated silsesquioxane; (2) 10 g of carboxylated silsesquioxane and 25 mL of deionized water were mixed, 1 g of hydrotalcite powder was added, and ultrasonic treatment was performed for 15 min to obtain a suspension; the suspension was added to 7.5 g of carboxylated silsesquioxane, and stirred at 65 °C for 1 h to obtain a carboxylated hydrotalcite; (3) 2.5 g of carboxylated hydrotalcite, 1.4 g of hydroxyl-containing triazine ultraviolet absorber, and 50 mL of toluene were mixed, 0.1 g of p-toluenesulfonic acid was added, and the temperature was raised to 110 °C and kept for 2 h to obtain a composite hydrotalcite; The preparation of the hydroxyl-containing s-triazine ultraviolet absorber comprises the following steps: A. Mix 9.2g cyanuric chloride and 125mL chlorobenzene, add 20g anhydrous aluminum chloride in an ice water bath, stir for 30min, add 10.6g m-xylene, keep warm for 3h, add 100mL 2% dilute hydrochloric acid, extract twice with 100mL chlorobenzene, dry, rotary evaporate, cool, and filter to obtain 2-chloro-4,6-di(2',4'-dimethylphenyl)-1,3,5-s-triazine; B. Mix 9.7g 2-chloro-4,6-bis(2',4'-dimethylphenyl)-1,3,5-s-triazine and 100mL chlorobenzene, add 4g anhydrous aluminum chloride in an ice-water bath, stir for 30min, add 3.6g resorcinol, heat to 82℃ and keep warm for 1h, add 100mL 2% dilute hydrochloric acid, distill, filter, and recrystallize twice with toluene to obtain 2-(2',4'-dihydroxyphenyl)-4,6-bis(2',4'-dimethylphenyl)-1,3,5-s-triazine; C. Mix 4g 2-(2',4'-dihydroxyphenyl)-4,6-bis(2',4'-dimethylphenyl)-1,3,5-s-triazine, 35mL N,N-dimethylformamide, and 0.5g sodium hydroxide, heat to 82°C in a water bath, add 1.2g epichlorohydrin, keep warm for 6h, reduce pressure, add 100mL ammonium chloride aqueous solution, extract with dichloromethane 3 times, dry, concentrate, and recrystallize with ethanol and dichloromethane solution with a volume ratio of 10:1 to obtain 2-(4,6-bis(2',4'-dimethylphenyl)-1,3,5-triazine-2-yl)-5-glycidyl ether phenol; D. Mix 4.5 g of 2-(4,6-bis(2',4'-dimethylphenyl)-1,3,5-triazine-2-yl)-5-glycidyl ether phenol, 50 mL of N,N-dimethylformamide, 0.8 g of ethyltriphenylphosphonium bromide, 1.5 g of n-dodecanol, and 0.8 g of n-tridecanol, heat to 92°C in a water bath and keep warm for 22 h, reduce the pressure, add 75 mL of deionized water, extract with ethyl acetate, dry, concentrate, reflux with ethanol for 20 min, and cool to obtain a hydroxyl-containing s-triazine ultraviolet absorber.

[0025] Comparative Example 1: Example 3 was used as the control group, and the composite hydrotalcite was replaced by the hydrotalcite, and the other processes were normal.

[0026] Comparative Example 2: Taking Example 3 as the control group, dioctyl phthalate (99%) was used to replace the modified hyperbranched polyester plasticizer, and the other processes were normal.

[0027] The preparation of hydrotalcite-like powder in the embodiments and comparative examples comprises the following steps: Solution A was prepared by mixing 6.7 g of magnesium chloride hexahydrate, 4 g of aluminum chloride hexahydrate, and 50 mL of deionized water. Solution B was prepared by mixing 2 g of sodium hydroxide, 1.2 g of sodium carbonate, and 50 mL of deionized water. Solutions A and B were dropped into a large beaker while stirring, the pH was adjusted to 10, and the mixture was aged at 80° C. for 12 h, washed with water, dried, and ground to obtain a hydrotalcite-like powder.

[0028] Sources of raw materials used (for demonstration purposes only): Polyvinyl chloride resin C2000: Dongguan Jinshixiang Plastic Raw Materials Co., Ltd.; ACR additives (acrylic additives): Japan Kaneka Chemical Industry Co., Ltd.; oxidized polyethylene wax ZC-316A: Jiaxing Zhongcheng Environmental Protection Technology Co., Ltd.; 2-carboxyethyl phenylphosphinic acid S70357: Shanghai Yuanye Biotechnology Co., Ltd.; ethylene bis stearamide N159314, methyl mercaptan tin M304039, 1,1,1-trimethylolpropane T110597, vinyl trimethoxysilane V162969, methacrylic acid M434201, trimer Chlorocyanide C118499, m-xylene X103350, resorcinol R661274, epichlorohydrin E108182, ethyltriphenylphosphonium bromide E110246, n-dodecanol D112298, n-tridecanol T105003: Aladdin reagent; N,N-dimethylformamide, toluene, p-toluenesulfonic acid, acetone, hydrochloric acid, sodium dodecylsulfonate, ammonium persulfate, sodium hydrogen sulfate, chlorobenzene, anhydrous aluminum chloride, sodium hydroxide, ammonium chloride, magnesium chloride hexahydrate, aluminum chloride hexahydrate, sodium carbonate, ethanol, dichloromethane, ethyl acetate, analytical grade, commercially available.

[0029] Performance test: The sheets prepared in the embodiments and comparative examples were tested: Impact resistance: The sheet size is 50mm long, 120mm wide and 2mm thick, and is characterized by notched impact strength, with reference to GB / T1043.1-2008 for testing; Flame retardancy: Conduct UL-94 vertical burning rating test; Aging resistance: The sample was irradiated with 365nm ultraviolet light for 168h, and the notched impact strength was measured again. If the change rate with the initial notched impact strength was 0-1% (including 1%), it was qualified, otherwise it was unqualified. The results are shown in Table 1. Table 1

[0030] The invention provides an aging-resistant polyvinyl chloride sheet and a preparation method thereof. The polyvinyl chloride sheet with good mechanical strength, high flame retardancy and aging resistance is prepared by optimizing components and processes.

[0031] By comparing Example 3 with Comparative Example 1, it can be seen that in the present invention, hydrotalcite-like materials are selected as fillers to improve the thermal stability and flame retardancy of the sheet. In order to further improve the uniformity of the dispersion of hydrotalcite-like materials in the sheet, the hydrotalcite-like materials are modified, and carboxylated silsesquioxane with flame retardant effect is selected as a modifier through the stripping and recombination method, in order to obtain synergistic flame retardancy, to obtain carboxylated hydrotalcite-like materials, and then a hydroxyl-containing s-triazine ultraviolet absorber is grafted, thereby greatly improving the flame retardancy and weather resistance of the sheet, improving the safety of the sheet, and extending the service life of the sheet.

[0032] By comparing Example 3 with Comparative Example 2, it can be seen that in order to improve the negative effects of the addition of a large amount of existing small molecule plasticizers, such as migration and decreased mechanical properties, and to simultaneously meet the requirements of improving processing fluidity, maintaining mechanical properties and improving aging resistance, the present invention uses 2-carboxyethylphenylphosphinic acid and 1,1,1-trimethylolpropane as raw materials to synthesize a hyperbranched polyester, which is then grafted with a hydroxyl-containing s-triazine ultraviolet absorber to obtain a modified hyperbranched polyester plasticizer for plasticizing polyvinyl chloride sheets, while greatly improving the flame retardancy and resistance of the sheets. Weathering resistance; the hydroxyl-containing s-triazine UV absorber is prepared from cyanuric chloride by a Friedel-Crafts reaction to generate 2-(2',4'-dihydroxyphenyl)-4,6-di(2',4'-dimethylphenyl)-1,3,5-s-triazine, which is then condensed with epichlorohydrin and then reacted with dodecanol and trialkyl alcohol. Compared with the common benzotriazole and benzophenone UV absorbers on the market, it has the advantages of strong UV absorption at 280-380nm, lighter color, high temperature resistance and better solubility.

[0033] The above descriptions are only embodiments of the present invention and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the present invention specification under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.

Claims

1. An aging-resistant polyvinyl chloride sheet, characterized in that: The invention comprises the following components in parts by weight: 88-102 parts of polyvinyl chloride resin, 2-4 parts of stabilizer, 6-9 parts of ACR additive, 3-7 parts of composite hydrotalcite, 5-10 parts of modified hyperbranched polyester plasticizer, 0.5-1 parts of ethylene bis stearamide and 0.2-0.6 parts of lubricant.

2. The aging-resistant polyvinyl chloride sheet according to claim 1, characterized in that: The stabilizer is one of an organic tin stabilizer and a liquid calcium zinc stabilizer or a combination thereof.

3. The aging-resistant polyvinyl chloride sheet according to claim 1, characterized in that: The lubricant is one or more of oxidized polyethylene wax, polyol ester and stearate.

4. The aging-resistant polyvinyl chloride sheet according to claim 1, characterized in that: The preparation of the modified hyperbranched polyester plasticizer comprises the following steps: 1) In a nitrogen atmosphere, 2-carboxyethylphenylphosphinic acid and 1,1,1-trimethylolpropane were mixed, the temperature was raised to 158-162°C and kept warm for 7-8 hours, the nitrogen was stopped, the vacuum was evacuated to 0.098MPa and kept warm for 2 hours, the mixture was poured out while hot, and cooled to obtain a hyperbranched polyester; 2) The hyperbranched polyester is heated to melt, and a mixture of a hydroxyl-containing triazine UV absorber, toluene, and p-toluenesulfonic acid is added, and the mixture is kept at 108-110°C for 5-6 hours, and the mixture is evacuated to 0.098 MPa, stirred for 1-2 hours, cooled, and dried to obtain a modified hyperbranched polyester plasticizer.

5. The aging-resistant polyvinyl chloride sheet according to claim 1, characterized in that: The preparation of the composite hydrotalcite-like material comprises the following steps: (1) Vinyl trimethoxysilane, acetone, concentrated hydrochloric acid and deionized water are mixed, kept at 40-50°C for 44-48 hours, washed and filtered to obtain vinyl silsesquioxane; vinyl silsesquioxane, methacrylic acid, sodium dodecyl sulfonate and deionized water are mixed, ultrasonically treated for 10-15 minutes, ammonium persulfate is added, kept at 55-65°C for 25-35 minutes, ammonium persulfate, sodium bisulfate, deionized water and methacrylic acid are added, and kept warm for 3-4 hours to obtain carboxylated silsesquioxane; (2) Mixing carboxylated silsesquioxane and deionized water, adding hydrotalcite-like powder, and ultrasonically treating for 10-15 minutes to obtain a suspension; adding the suspension to carboxylated silsesquioxane, stirring at 55-65° C. for 1-2 hours, and drying to obtain a carboxylated hydrotalcite-like powder; (3) Mix the carboxylated hydrotalcite, the hydroxyl-containing s-triazine ultraviolet absorber and toluene, add p-toluenesulfonic acid, raise the temperature to 108-110°C and keep it for 2-3 hours to obtain a composite hydrotalcite.

6. The aging-resistant polyvinyl chloride sheet according to claim 4, characterized in that: The mass ratio of the hyperbranched polyester to the hydroxyl-containing s-triazine ultraviolet absorber is 11:

3.

7. The aging-resistant polyvinyl chloride sheet according to claim 5, characterized in that: The mass ratio of the carboxylated hydrotalcite to the hydroxyl-containing s-triazine ultraviolet absorber is 2.5:1.

4.

8. An ageing-resistant polyvinyl chloride sheet according to claim 4 or 5, characterized in that: The preparation of the hydroxyl-containing s-triazine ultraviolet absorber comprises the following steps: A. Mix cyanuric chloride and chlorobenzene, add anhydrous aluminum chloride in an ice water bath, stir for 20-30 minutes, add m-xylene, keep warm for 2-3 hours, add dilute hydrochloric acid, extract with chlorobenzene twice, dry, rotary evaporate, cool, and filter to obtain 2-chloro-4,6-di(2',4'-dimethylphenyl)-1,3,5-s-triazine; B. Mix 2-chloro-4,6-di(2',4'-dimethylphenyl)-1,3,5-s-triazine and chlorobenzene, add anhydrous aluminum chloride in an ice-water bath, stir for 20-30 minutes, add resorcinol, heat to 78-82℃ and keep warm for 1-2 hours, add dilute hydrochloric acid, distill, filter, and recrystallize twice with toluene to obtain 2-(2',4'-dihydroxyphenyl)-4,6-di(2',4'-dimethylphenyl)-1,3,5-s-triazine; C. Mix 2-(2',4'-dihydroxyphenyl)-4,6-bis(2',4'-dimethylphenyl)-1,3,5-s-triazine, N,N-dimethylformamide and sodium hydroxide, heat to 78-82°C in a water bath, add epichlorohydrin, keep warm for 5-6h, reduce pressure, add aqueous ammonium chloride solution, extract with dichloromethane for 3 times, dry, concentrate, recrystallize with ethanol and dichloromethane solution with a volume ratio of 10:1 to obtain 2-(4,6-bis(2',4'-dimethylphenyl)-1,3,5-triazine-2-yl)-5-glycidyl ether phenol; D. Mix 2-(4,6-bis(2',4'-dimethylphenyl)-1,3,5-triazine-2-yl)-5-glycidyl ether phenol, N,N-dimethylformamide, ethyltriphenylphosphonium bromide, n-dodecanol and n-tridecanol, heat to 88-92°C in a water bath and keep warm for 22-24 hours, reduce the pressure, add deionized water, extract with ethyl acetate, dry and concentrate, reflux with ethanol for 10-20 minutes, cool and obtain a hydroxyl-containing s-triazine ultraviolet absorber.

9. A method for preparing an ageing-resistant polyvinyl chloride sheet according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: putting polyvinyl chloride resin, stabilizer, ACR auxiliary agent, modified hyperbranched polyester plasticizer, composite hydrotalcite, ethylene bis stearamide and lubricant into a high-speed mixer, mixing and stirring evenly, and then extruding and granulating, and pressing and tableting to obtain an aging-resistant polyvinyl chloride sheet.

10. The method for preparing an ageing-resistant polyvinyl chloride sheet according to claim 9, characterized in that: Working conditions of high-speed mixer: preheat to 118℃ before adding materials.

Citation Information

Patent Citations

  • Preparation method of trimethylolpropane tri-(2-carboxyethyl phenyl phosphinate)

    CN102351899A

  • Aging-resistant polyvinyl chloride plastic

    CN107236216A

  • High-impact resistance polyvinyl chloride water supply tube and production method thereof

    CN107540975A

  • Method of preparing long carbon chain triazine ultraviolet absorber containing ether bond at low temperature

    CN109438377A

  • PVC composition with dimensional stability

    CN110724353A

Cited By

  • Weather-resistant water-based varnish and preparation method thereof

    CN120484601A